Living with asthma and chronic obstructive airways disease: Using technology to support self-management – An overview. (November 2017) - Morrison, Deborah; Mair, Frances S; Yardley, Lucy; Kirby, Sarah; Thomas, Mike
Long-term respiratory conditions such as asthma and chronic obstructive pulmonary disease (COPD) are common, and cause high levels of morbidity and mortality. Supporting self-management is advocated for both asthma and increasingly so for COPD, and there is growing interest in the potential role of a range of new technologies, such as smartphone apps, the web or telehealth to facilitate and promote self-management in these conditions. Treatment goals for both asthma and COPD include aiming to control symptoms, maintain activities, achieve the best possible quality of life and minimize risks of exacerbation. To do this, health professionals should be (a) helping patients to recognize deteriorating symptoms and act appropriately; (b) promoting adherence to maintenance therapy; (c) promoting a regular review where triggers can be established, and strategies for managing such triggers discussed; and (d) promoting healthy lifestyles and positive self-management of symptoms. In particular, low uptake of asthma action plans is a modifiable contributor to morbidity and possibly also to mortality in those with asthma and should be addressed as a priority. Using technology to support self-management is an evolving strategy that shows promise. This review provides an overview of self-management support and discusses how newer technologies may help patients and health professionals to meet key treatment goals.